Study of the effect of multiple phase transformations and relaxation annealing on the microstructure of a martensitic TiNi alloy in different structural states - Anna Churakova; Elmira Iskhakova (Annals of Mathematics and Physics - Peertechz Publications, 2023)
The work was devoted to studying the effect of multiple phase transformations in the temperature range of phase transformations of a TiNi alloy with a martensitic structure in various initial states - coarse-grained, ultrafine-grained, nanostructured. The conducted studies have shown that in the process of thermal cycling, the accumulation of defects in the crystalline structure occurs - dislocations, which contribute to a decrease in the size of structural elements. Subsequent relaxation annealing, slightly reducing the dislocation density, made it possible to obtain a stable and more equilibrium microstructure, including the nanostructural state.